2009
DOI: 10.1007/s00520-009-0649-8
|View full text |Cite
|
Sign up to set email alerts
|

Early switching from morphine to methadone is not improved by acetaminophen in the analgesia of oncologic patients: a prospective, randomized, double-blind, placebo-controlled study

Abstract: Objectives This study aims to evaluate the efficacy of methadone as substitute for morphine and to investigate if the addition of acetaminophen could reduce the time to attain an equianalgesic dose of methadone and/or to improve the level of pain control in oncologic patients. Patients and methods Fifty patients on stable doses of morphine for 1 week were switched to methadone using a "stop-start" strategy and randomized in a double-blind fashion to receive either acetaminophen (750 mg PO every 6 hours) or pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 26 publications
0
21
0
1
Order By: Relevance
“…A further four out of six studies, with a combined patient population of 141, were not able to show a further increase in analgesic effect when 650–1000 mg of acetaminophen (3–5 g/day) was combined with step III opioids . Merely two studies, comprising 50 patients, were able to show a positive effect.…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…A further four out of six studies, with a combined patient population of 141, were not able to show a further increase in analgesic effect when 650–1000 mg of acetaminophen (3–5 g/day) was combined with step III opioids . Merely two studies, comprising 50 patients, were able to show a positive effect.…”
Section: Resultsmentioning
confidence: 88%
“…No differences in side effects were found when acetaminophen was combined with a strong opioid compared with a placebo . A direct comparison of acetaminophen alone vs. butorphanol or acetaminophen + butorphanol showed that only the combined preparation delivered significantly superior analgesia compared with placebo…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Finally, paracetamol was used to assist opioid switching from morphine to methadone in a randomized, doubleblind, placebo-controlled study [17]. Whatever the reason for switching, possibly uncontrolled pain and/or adverse effects, 50 patients having unfavorable balance between pain and adverse effects, did not changed their analgesic regimen for one week.…”
Section: Paracetamolmentioning
confidence: 99%
“…A more recent systematic review, based on 4 RCTs published after the 2007 Cochrane review, showed no difference in effectiveness between methadone compared to other strong opioids in 2 RCTs . Two other RCTs used in this systematic review evaluated the effect of opioid rotation to methadone: in one study no conclusion on the efficacy of methadone in treatment of cancer pain could be presented due to the number of dropouts, and the other reported a decrease in pain intensity switching from morphine to methadone and a patient preference for methadone . It is important to realize that these studies were performed to show superiority instead of noninferiority of one drug over another.…”
Section: Discussionmentioning
confidence: 91%